Exploration of Pattern Recognition Receptor Agonists as Candidate Adjuvants - Ong, Guang Han; Lian, Benedict Shi Xiang; Kawasaki, Takumi; Kawai, Taro (Frontiers in Cellular and Infection Microbiology, 2021)
Adjuvants are used to maximize the potency of vaccines by enhancing immune reactions. Components of adjuvants include pathogen-associated molecular patterns (PAMPs) and damage-associate molecular patterns (DAMPs) that are agonists for innate immune receptors. Innate immune responses are usually activated when pathogen recognition receptors (PRRs) recognize PAMPs derived from invading pathogens or DAMPs released by host cells upon tissue damage. Activation of innate immunity by PRR agonists in adjuvants activates acquired immune responses, which is crucial to enhance immune reactions against the targeted pathogen. For example, agonists for Toll-like receptors have yielded promising results as adjuvants, which target PRR as adjuvant candidates. However, a comprehensive understanding of the type of immunological reaction against agonists for PRRs is essential to ensure the safety and reliability of vaccine adjuvants. This review provides an overview of the current progress in development of PRR agonists as vaccine adjuvants, the molecular mechanisms that underlie activation of immune responses, and the enhancement of vaccine efficacy by these potential adjuvant candidates.